Trade liberalization and South African manufacturing: Looking back with data - Ciaran F. Driver (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper provides a retrospective assessment of the effects of trade policies on South African manufacturing since the transition to democracy, examining the differences and commonalities in the views of economists in favour of and against an acceleration of trade liberalization. Data from the Bureau of Economic Research are used to test a number of effects on manufacturing industry that were envisaged to flow from trade policy reforms, including effects on mark-ups, productivity, exports, employment, and investment. The evidence presented here shows that a rising real exchange rate results in falling unit raw material costs as expected. However, exporter profitability still suffers because the mark-up also falls, presumably to keep prices from rising too much in foreign currencies. There is evidence, too, that a real appreciation causes the export volume to decrease.
Keywords: E24; E65; F41; 330; manufacturing; trade policy; trade liberalization; South African economy